Towards adjustments in university rankings, computer science field - Sobral, Sónia Rolland (2020)
Every year we are flooded with different university rankings that are available to everyone in the internet: pre-college youths and their families, teachers/researchers, and investors/governments eagerly consult these lists. A university ranking is a system that lists some universities according to certain items and weights. These items can be scientific production, awards received by staff or alumni, or based on credibility reports. Each ranking gives importance to different characteristics and the corresponding result is also very different. Those who read the result of these rankings often do not know how they are created and become confused with such diversity. (...)